2018
DOI: 10.3847/1538-4357/aacd10
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Activity and Quiescence of High-redshift Cluster Environments: ALMA Observations of Cl J1449+0856 at z = 2

Abstract: We present ALMA observations of the 870µm continuum and CO(4-3) line emission in the core of the galaxy cluster ClJ1449+0856 at z = 2, a NIR-selected, X-ray detected system in the mass range of typical progenitors of today's massive clusters. The 870µm map reveals six F 870µm > 0.5 mJy sources spread over an area of 0.07arcmin 2 , giving an overdensity of a factor ∼ 10 (6) with respect to blank field counts down to F 870µm > 1 mJy (> 0.5 mJy). On the other hand, deep CO(4-3) follow-up confirms membership of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 131 publications
(179 reference statements)
1
30
0
Order By: Relevance
“…We stress here that the BCG candidate of the cluster Cl J1449+0856 at z = 2 was first described by Gobat et al (2011) and has recently been observed with ALMA Strazzullo et al 2018). No stellar mass estimate is reported for this source in these studies.…”
Section: Molecular Gas Diagramsmentioning
confidence: 77%
“…We stress here that the BCG candidate of the cluster Cl J1449+0856 at z = 2 was first described by Gobat et al (2011) and has recently been observed with ALMA Strazzullo et al 2018). No stellar mass estimate is reported for this source in these studies.…”
Section: Molecular Gas Diagramsmentioning
confidence: 77%
“…Webb et al (2017) recently detected CO(2→1) with the Large Millimeter Telescope (LMT), which is associated with a large reservoir (∼ 10 11 M ) of molecular gas that is possibly associated with the BCG and/or its nearby cluster core companions within the 25 arcsec diameter (i.e., ∼ 200 kpc at z = 1.7) beam of the LMT. By spatially resolving, both in continuum and in CO, the BCG from each of its nearby companions separately, the present study the present study is one of the first to probe both molecular gas and dust reservoirs of z 1 BCGs in detail (Emonts et al 2013(Emonts et al , 2016Coogan et al 2018;Strazzullo et al 2018;Castignani et al 2019). We thus aim to unveil the mechanisms at play for the assembly and the star formation fueling of the most distant BCGs.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, massive galaxy clusters must have formed the bulk of their member galaxies' stellar mass at early times (e.g., Archibald et al 2001;Hopkins & Beacom 2006). At high-redshift, a significant amount of enhancement of star formation is observed in galaxies residing in candidate protoclusters -the progenitors of massive local galaxy clusters (e.g., Steidel et al 2000;Geach et al 2005;Chapman et al 2009;Capak et al 2011;Muzzin et al 2011;Clements et al 2014;Smail et al 2014;Webb et al 2013;Casey et al 2015;Ma et al 2015;Daddi et al 2017;Umehata et al 2017;Stach et al 2017Stach et al , 2018Strazzullo et al 2018). Thus, there is some evidence that at high redshift, galaxy evolution is accelerated at early times in regions of strong overdensity.…”
Section: Introductionmentioning
confidence: 99%